EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN PENDEKATAN ISLAM DALAM MENINGKATKAN CURIOSITY SISWA - Anisatun Murtafiah (Institut Agama Islam Syubbanul Wathon Magelang, 2023)
This study aims to determine the effectiveness of group guidance services with an Islamic approach in increasing students' curiosity. This study uses a type of experimental quantitative research, the data source comes from 27 students with a data collection method in the form of a questionnaire. The data analysis technique in this study used SPSS version 22.0 with the Shapiro Wilk test, which obtained a sig. (2 tailed) and interpretation of the results using the paired sample test. The results of this study indicate that there is an increase in the results of the post test. So it can be concluded that Ho is rejected Ha is accepted.